(untitled) - Ash, Carol (New York, 1986)
This book fills an educational void by adapting unique classroom-tested techniques that students find most congenial...that strip the shroud of mystery from an esoteric subject...that prepare students for applications of calculus in later courses.
Keywords: Calculus,Tính toán